2024
DOI: 10.1001/jamahealthforum.2024.0302
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Use of Hepatitis C Direct-Acting Antivirals After Access Restrictions Were Eased by State Medicaid Programs

Sonya Davey,
Kevin Costello,
Massimiliano Russo
et al.

Abstract: ImportanceDirect-acting antivirals (DAAs) are safe and highly effective for curing hepatitis C virus (HCV) infection, but their high cost led certain state Medicaid programs to impose coverage restrictions. Since 2015, many of these restrictions have been lifted voluntarily in response to advocacy or because of litigation.ObjectiveTo estimate how the prescribing of DAAs to Medicaid patients changed after states eased access restrictions.Design, Setting, and ParticipantsThis modified difference-in-differences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In some cases, this could lead states to restrict patient access to highly effective and potentially life-saving therapies. For example, many state Medicaid programs restricted access to curative hepatitis C antivirals to prevent catastrophic surges in spending, which slowed the uptake of an important but costly public health intervention . More recently, in April 2024, the North Carolina State Health Plan opted to remove coverage of new highly effective antiobesity medications to prevent premiums from climbing by nearly $50 a month .…”
Section: Implications For Patientsmentioning
confidence: 99%
“…In some cases, this could lead states to restrict patient access to highly effective and potentially life-saving therapies. For example, many state Medicaid programs restricted access to curative hepatitis C antivirals to prevent catastrophic surges in spending, which slowed the uptake of an important but costly public health intervention . More recently, in April 2024, the North Carolina State Health Plan opted to remove coverage of new highly effective antiobesity medications to prevent premiums from climbing by nearly $50 a month .…”
Section: Implications For Patientsmentioning
confidence: 99%
“…Previous studies have demonstrated a relative increase in DAA prescriptions following the lifting of DAA restrictions. 12 , 13 , 14 , 15 However, an assessment of the overall association between Medicaid expansion and these restrictions with the rate of people with Medicaid treated for hepatitis C nationwide may inform decisions to remove persistent prior authorization requirement. Furthermore, the historical experience of implementing DAA prior authorization requirements to prioritize hepatitis C treatment among certain groups may inform future decisions around implementing prior authorization for treatment of other conditions with public health implications.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated a relative increase in DAA prescriptions following the lifting of DAA restrictions . However, an assessment of the overall association between Medicaid expansion and these restrictions with the rate of people with Medicaid treated for hepatitis C nationwide may inform decisions to remove persistent prior authorization requirement.…”
Section: Introductionmentioning
confidence: 99%